False discoveries in volatility timing of mutual funds - Kim, Sangbae; In, Francis (Journal of Banking & Finance, 2012)
This paper examines the volatility timing of US mutual funds by controlling the false discovery rate to find out how many funds are truly countercyclical (procyclical) timing funds. Empirical results show that, given the whole universe of our sample funds, the percentages of countercyclical and procyclical volatility timing funds are about equal. We also find that while the standard approach, which simply counts the number of significant positive (negative) timing coefficients, does not incorporate false discoveries in volatility timing, it provides quite accurate volatility timing results. Finally, we find that the performance measures for an equally weighted portfolio of procyclical timing funds are greater than for an equally weighted portfolio of countercyclical timing funds in the in-sample test, consistent with our expectation that procyclical timers earn higher returns because they take on more risk. However, the countercyclical timing portfolio outperforms the procyclical timing portfolio in the out-of-sample test.